Paraneoplastic syndrome – a rare but treatable cause of non-thyroid-related extraocular muscle enlargement. (2nd November 2019) - Kumar, S.; Diamond, T.
ABSTRACT: Paraneoplastic syndrome is a rare but reversible cause of non-thyroid-related extraocular muscle enlargement. We present a 71-year-old lady with diplopia, restricted eye movements, suppressed thyroid-stimulating hormone and enlargement of all extraocular muscles while on thyroxine replacement for hypothyroidism. She had distant history of metastatic breast cancer treated with chemotherapy, surgical resection and tamoxifen. She had negative anti-thyroid autoantibodies and thyroid ultrasound was not consistent with autoimmune thyroid disease. Carcinoembryonic antigen and cancer antigens 15-3, 125 and 72-4 were elevated, and whole-body positron emission tomography-computed tomography showed avid liver, left adrenal and skeletal lesions, with liver biopsy confirming breast cancer recurrence. She received prednisone and chemotherapy (letrozole, palbociclib) and achieved normalisation of eye movements and reduction in her EOME at 9-month follow-up. Our case highlights the importance of exploring paraneoplastic syndrome as a treatable cause of EOME in a patient lacking features of thyroid orbitopathy and autoimmune thyroid disease.